Isolation and characterization of pathogenic Klebsiella pneumoniae strains from lettuce: a potential source of antibiotic resistance and development of a mathematical model for ANOVA results - Khan, Ruby; Wali, Saima; Khan, Sumbal; Munir, Shaista; Pari, Bakht; Yousuf, Amjad M.; Almutawif, Yahya A. (Frontiers in Microbiology, 2024)
Introduction This study aimed to evaluate the prevalence of Klebsiella pneumoniae contamination in raw lettuce from Risalpur, Pakistan, and to analyze the antibiotic susceptibility profiles of the isolated strains. The presence of foodborne pathogens such as K. pneumoniae poses significant public health risks, particularly in regions with suboptimal hygiene practices and improper food handling. Methods Lettuce samples were collected from various sources in Risalpur and screened for K. pneumoniae. Antimicrobial susceptibility testing was performed to evaluate the effectiveness of various antibiotics against the isolated strains. Statistical analyses, including ANOVA and linear regression, were conducted to assess differences in inhibition zones and to predict antibiotic effectiveness based on concentration. Results The results revealed a significant prevalence of K. pneumoniae in the lettuce samples, highlighting the risks associated with poor hygiene, transportation, storage, and contaminated irrigation water. The isolated strains exhibited high susceptibility to gentamicin but demonstrated notable resistance to doxycycline, vancomycin, and ticarcillin. Multidrug-resistant (MDR) strains were identified. ANOVA showed significant differences in inhibition zones, and the linear regression model predicted a Zone of Inhibition based on antibiotic concentration (β0 = 10.6667, β1 = 0.4556). Discussion The identification of MDR strains of K. pneumoniae underscores the urgent need for enhanced antibiotic stewardship and food safety protocols to manage foodborne pathogens. Improved hygiene practices throughout the food production and supply chain are critical to mitigate health risks and address the challenge of growing antibiotic resistance.